2016
DOI: 10.1177/0884533616680355
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Is Highly Prevalent in Older Medical Patients With Mobility Limitation

Abstract: Patients with dependent ambulatory status experienced a higher prevalence of sarcopenia compared with those with ambulation; in addition, decline in ambulatory status was an independent indicator for the presence of sarcopenia after adjustment for potential confounders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…CC measures not only muscle mass but also bone, subcutaneous adipose, and skin. It is not surprising that the cut-off values in this study were lower because compared with healthy adults, hospitalized patients tend to have an increased malnutrition risk [10,17,18,19] and elderly patients are likely to have thin subcutaneous adipose layers and skin. Therefore, we propose that the CC cut-off values determined in this study would be most useful clinically in hospitalized elderly patients.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…CC measures not only muscle mass but also bone, subcutaneous adipose, and skin. It is not surprising that the cut-off values in this study were lower because compared with healthy adults, hospitalized patients tend to have an increased malnutrition risk [10,17,18,19] and elderly patients are likely to have thin subcutaneous adipose layers and skin. Therefore, we propose that the CC cut-off values determined in this study would be most useful clinically in hospitalized elderly patients.…”
Section: Discussionmentioning
confidence: 84%
“…SMM was measured using BIA in the supine position using a multi-frequency segmental BIA instrument [9] (Inbody S10, Inbody, Tokyo, Japan), which is the latest version of a validated instrument that uses 6 different frequencies [10]. Skeletal muscle mass index (SMI) was calculated as the measured appendicular muscle mass divided by height squared (kg/m 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, Rodríguez-Rejón et al (34) and Salvà et al (25) also used EWGSOP methodology and identical diagnostic methods and cutoffs in their studies of Spanish old people's homes but, despite applying the same age inclusion criterion (age >70 y), reported very different prevalence values (68% and 37%, respectively). One influential factor may be that individuals with cognitive impairment or inability to walk, known risk factors for sarcopenia (43,44), were included by Rodríguez-Rejón et al (34) but excluded by Salvà et al (25).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the poorest oral health at admission were related to old age, malnutrition, decreased ADL, and impaired cognition. All of these variables are considered to be related to sarcopenia [17,21,22], which is independently associated with poor outcomes, such as mortality, in older adults [23]. Interventions against sarcopenia such as nutritional therapy and rehabilitative exercise along with appropriate oral care intervention may reduce mortality in patients with poor oral health.…”
Section: Discussionmentioning
confidence: 99%